A specific tongue microbiota signature is found in patients displaying an improvement of orosensory lipid perception after a sleeve gastrectomy - Bernard, Arnaud; Radoi, Loredana; Christensen, Jeffrey; Servant, Florence; Blasco-Blaque, Vincent; Ledoux, Séverine; Collet, Xavier; Besnard, Philippe (Frontiers in Nutrition, 2023)
A preferential consumption of low-fat foods is reported by most of the patients after a vertical sleeve gastrectomy (VSG). The fact that a recent study shed light on a relationship between oral microbiota and fat taste sensitivity in obese patients prompted us to explore whether such a connection also exists in the context of a VSG. Thirty-two adult female patients with a severe obesity (BMI = 43.1 ± 0.7kg/m2) and candidates for a VSG were selected. Oral microbiota composition surrounding the gustatory circumvallate papillae (CVP) and the lipid perception thresholds were explored before and 6 months after surgery. VSG was found to be associated both with a qualitative (compositional changes) and quantitative (lower gene richness) remodeling of the peri-CVP microbiota. Analysis of the lipid perception allowed us to distinguish two subgroups: patients with a post-operative improvement of the fat taste sensitivity (i.e. with a lower threshold, n=14) and unimproved patients (n=18). Specific peri-CVP microbiota signatures also discriminated these two subgroups, unimproved patient being characterized by higher levels of Porphyromonas, Fusobacterium and Haemophilus genera associated with lower levels of Atopobium and Prevotella genera as compared to the lipid-improved patients. Collectively, these data raise the possibility that the microbial environment surrounding gustatory papillae might play a role in the positive changes of fat taste sensitivity observed in some patients after VSG.